2007
DOI: 10.1111/j.1468-1331.2007.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of impaired T‐ and B‐cell compartments on efficacy of IVIg in dysimmune neuropathies

Abstract: Autoimmune mechanisms are postulated to play a role in the development and progression of dysimmune neuropathies (DN). We investigated the relation between lymphocyte number and marker expression, and disease activity in 20 patients with DN under intravenous immunoglobulins (IVIg) treatment. B-and T-lymphocyte markers were studied by flow cytometry of the expression of CD5, CD25, CD23 and CD38 markers on B cells and of CD3, CD4 and CD8 markers, respectively. These parameters were compared with those obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
1
2
Order By: Relevance
“…We found a significant reduction in plasma cells of CIDP patients with IVIg and steroid treatments, as well as untreated active CIDP patients, in contrast to two previous studies [ 24 , 25 ]. The study of Mata and colleagues consisted of patients with various dysimmune neuropathies including CIDP patients [ 24 ], whereas the study of Kuhnke et al reported markedly elevated plasma cell numbers in eight untreated CIDP patients and a significant decrease by IVIg treatment in six patients [ 25 ]. Similarly, our untreated CIDP patients showed relatively higher plasma cell ratios than steroid- and IVIg-treated patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found a significant reduction in plasma cells of CIDP patients with IVIg and steroid treatments, as well as untreated active CIDP patients, in contrast to two previous studies [ 24 , 25 ]. The study of Mata and colleagues consisted of patients with various dysimmune neuropathies including CIDP patients [ 24 ], whereas the study of Kuhnke et al reported markedly elevated plasma cell numbers in eight untreated CIDP patients and a significant decrease by IVIg treatment in six patients [ 25 ]. Similarly, our untreated CIDP patients showed relatively higher plasma cell ratios than steroid- and IVIg-treated patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, CD3 + T cells were significantly decreased in CIDP patients with IVIg or steroid treatment compared to the untreated group, as previously reported [ 24 , 33 ]. By contrast, immune treatments failed to make a significant reversion in B-cell dysregulation in our CIDP patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of those, reduced numbers of CD32b expressing memory B cells and monocytes, as well as increased numbers of CD16 + myeloid dendritic cells, were associated with disease activity and/or poor response to immunoglobulin therapy (Tackenberg et al 2009;Dyer et al 2016). Other studies demonstrated that CIDP is associated with a reduction of regulatory T cells, as well as with an increase of monocytes (Matà et al 2007;Sanvito et al 2009).…”
Section: Introductionmentioning
confidence: 99%